2014
DOI: 10.1186/1752-1947-8-400
|View full text |Cite
|
Sign up to set email alerts
|

Monoaural musical hallucinations caused by a thalamocortical auditory radiation infarct: a case report

Abstract: IntroductionMusical hallucinations are complex auditory perceptions in the absence of an external acoustic stimulus and are often consistent with previous listening experience. Their causation can be classified as associated with either psychiatric disorders, such as schizophrenia, or organic disorders, such as epilepsy or sensorineural deafness. Non-epileptic musical hallucinosis due to lesions of the central auditory pathway, especially of the thalamocortical auditory radiation, is rare.Case presentationWe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Furthermore, theoretical and empirical studies have proposed that deficient connectivity and abnormal patterns of activity in TC projections contribute to the pathogenesis of the disease 5255 . Moreover, a local ischemic infarction that disrupts auditory TC projections in a nonpsychotic patient can cause auditory hallucinations 56 . 3) Sensitivity to antipsychotics is observed in the auditory but not the visual or somatosensory TC projections of 22q11DS mice, which is consistent with clinical observations of the substantially higher prevalence of auditory hallucinations, compared with that of hallucinations in other sensory modalities, in schizophrenia 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, theoretical and empirical studies have proposed that deficient connectivity and abnormal patterns of activity in TC projections contribute to the pathogenesis of the disease 5255 . Moreover, a local ischemic infarction that disrupts auditory TC projections in a nonpsychotic patient can cause auditory hallucinations 56 . 3) Sensitivity to antipsychotics is observed in the auditory but not the visual or somatosensory TC projections of 22q11DS mice, which is consistent with clinical observations of the substantially higher prevalence of auditory hallucinations, compared with that of hallucinations in other sensory modalities, in schizophrenia 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Because the evidence for abnormal thalamocortical connections is so overwhelming ( Silbersweig et al, 1995 ; Ferrarelli and Tononi, 2011 ; Smith et al, 2011 ; Sodhi et al, 2011 ), some researchers have suggested that schizophrenia is a disease of disrupted thalamocortical neuronal networks ( Cronenwett and Csernansky, 2010 ). Noteworthy, a local ischemic infarction that disrupted neural connections emanating from the auditory part of the thalamus and projecting to the auditory cortex (auditory thalamocortical projections) in a previously non-psychotic individual with no prior neurological symptoms caused transient auditory (musical) hallucinations that occurred acutely postinfarction ( Woo et al, 2014 ). The hallucinations were intermittent, lasted several minutes, occurred when the environment was quiet, and discontinued or reduced in volume when the individual was engaged in conversation.…”
Section: Thalamic Abnormalities In Schizophreniamentioning
confidence: 99%
“…Also, there is evidence that AR infarct can cause auditory hallucination ( Woo et al, 2014 ), and that the extra-lemniscal pathway might be implicated in tinnitus perception ( Moller et al, 1992 ). At present, studies investigating the auditory pathways in these patients relied on WM ROI measurements ( Lee et al, 2007 ; Lin et al, 2008 ), which only outline a portion of the underlying WM bundles and may not be representative of the entire tract.…”
Section: The Acoustic Radiation: Functional and Clinical Implicationsmentioning
confidence: 99%